An experimental study of application of activated carbon from nipa fruit waste on herbal drinks. Issue 1 (31st December 2023) - Wijana, Susinggih; Atikah, Husna; Kartikaningrum, Widhistya; Pranowo, Dodyk; Setyawan, Hendrix Yulis
ABSTRACT: Nipa is one of the palm family, and 60% of the fruit is biomass waste. One of the utilizations of the waste is to be converted into activated carbon. In the present research, the nipa waste was pyrolyzed, and the biochar, a by-product of the pyrolysis process, was activated using HCl. The nipa's fruit waste activated carbon (NWAC) was then experimentally used to remove the distinct odours of Noni and Mangosteen herbal drinks. The characteristics of the NWAC produced in this study have a water content of 15.08%, ash content of 8.77%, volatile matter of 8.51%, carbon content of 67.6%, yield of 95.49%, iodine adsorption of 966.98 mg/g, and surface area of 1066.39 m 2 /g. The characteristics of the Noni herbal drink after NWAC adsorption showed that the highest total dissolved solids of 6.97 °Brix was treated with 25% NWAC addition. The lowest IC50 value was 4.4 ppm, and it was gradually increased with the addition of the NWAC. The addition of NWAC decreased the total phenol in the Mangosteen peel herbal drink, but the effect was insignificant in the Noni herbal drink. Antioxidant activity values ranged from 16% to 37% in the Mangosteen herbal drink, and 30% to 55% in the Noni herbal drink. The total dissolved solids ranged between 4 and 7 °Brix in both herbal drinks. Overall, the addition of NWAC improved the quality of the herbal drinks, but the optimum condition needs to be quantified.